Comprehensive evaluation of cardiovascular efficacy and safety outcomes of SGLT2 inhibitors in high risk patients of cardiovascular disease: systematic review and meta-analysis. Issue 2 (18th August 2020) - Bhattarai, Mukul; Salih, Mohsin; Regmi, Manjari; Al-akchar, Mohammad; Koester, Cameron; Ibrahim, Abdisamad; Parajuli, Priyanka; Garcia, Odalys Lara; Bhandari, Bishal; Rehman, Anis; Siddique, Momin
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To demonstrate a magnitude of the cardiovascular benefits, concomitantly analyzing the safety outcomes of sodium-glucose cotransporter 2 inhibitor (SGLT2-I) comprehensively, as a class effect in a larger sample size combined from recent randomized control trials. Methods: We searched electronic databases using specific terms and evaluated 6 efficacy and 10 safety outcomes. Odds ratios (ORs) and 95% confidence interval (CI) were used to compare two interventions. Results: Five studies ( n = 41 267) were included, among which 23 539 received SGLT2-I. The SGLT2-I group favored reduction in major adverse cardiovascular events (OR, 0.78; 95% CI, 0.62–0.98; P = 0.03), cardiovascular death (CVD) or heart failure hospitalization (OR, 0.60; 95% CI, 0.46–0.80; P = 0.0004), rate of hospitalization for heart failure (OR, 0.56; 95% CI, 0.44–0.72; P < 0.00001), CVD (OR, 0.68; 95% CI, 0.50–0.93; P = 0.01), all-cause mortality (OR, 0.67; 95% CI, 0.48–0.93; P = 0.02) and myocardial infarction (OR, 0.79; 95% CI, 0.64–0.99; P = 0.04) when compared to the placebo group. Safety analysis showed higher diabetic ketoacidosis (DKA) rate in SGLT2-I group (OR, 2.33; 95% CI, 1.40–3.90; P = 0.001); in contrast, major hypoglycemic events were significantly lower (OR, 0.79; 95% CI, 0.73–0.87; P < 0.00001). AKI was significantly higher in the placebo group (OR, 0.76; 95% CI, 0.65–0.88; P = 0.0004). There were no statistically significant effects on other outcomes. Conclusion: In selected high-risk patients of cardiovascular disease, the SGLT2-I is a potential effective class of drugs for improving cardiovascular outcomes and all-cause mortality without an increased risk of all other major complications except DKA on this meta-analysis.